THE ROLE OF BIOTECHNOLOGY IN KARAKALPAKSTAN: INNOVATIVE APPROACHES AND PROSPECTS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article examines the application of biotechnology in Karakalpakstan’s agricultural and ecological sectors. It discusses innovative approaches, current opportunities, and emerging challenges in using biotechnological solutions to enhance agricultural product quality, manage water resources, and restore the environment. The analysis also highlights locally adapted innovative methods and outlines the measures required to address regional issues.